Doing trinitarian theology: primary references to God and imagination - R. Venter (In die Skriflig, 2010)
This article explores methodology in trinitarian theology and proposes one possible avenue to the question of how it should be done. The basic argument highlights the multiple functions of references to God in theological discourse. Three of these po-tential ways are discussed, namely God as Agent, God as Model, and God as Heuristic Principle. The various references are explained with examples taken from Scripture and contem-porary trinitarian proposals. A picture emerges of sophisticated rhetorical strategies being employed by theologians. By iden-tifying some of the functions ofGod-references, the article not only emphasises the imaginative and constructive nature of theological reflection, but also contributes to the question of the possibilities of trinitarian theology and its development.